Plant, Soil and Microbes 2016
DOI: 10.1007/978-3-319-29573-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Root Exudates and Their Molecular Interactions with Rhizospheric Microbes

Abstract: Biologically important plant-microbe interactions are mediated by a wide array of signal compounds rhizodeposited from both plant and microbial species. Root exudates are some of the potentially important low molecular weight compounds secreted from plant roots. They are involved in building a network of biointeractions through several physical, chemical, or biological interactions. Application of bioinoculums has signifi cantly improved growth parameters and yield of many economically valued crops. Root exuda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 118 publications
(188 reference statements)
1
25
0
Order By: Relevance
“…Root exudates play key roles in plant-microbe interactions and root colonization by rhizobacteria [28]. Based on the fact that strain EGB could migrate towards cucumber roots in soil, we deduced that root exudates play a role in the recruitment of strain EGB to the rhizosphere.…”
Section: Chemotaxis Towards Root Exudates and Cucumber Root Colonizatmentioning
confidence: 95%
“…Root exudates play key roles in plant-microbe interactions and root colonization by rhizobacteria [28]. Based on the fact that strain EGB could migrate towards cucumber roots in soil, we deduced that root exudates play a role in the recruitment of strain EGB to the rhizosphere.…”
Section: Chemotaxis Towards Root Exudates and Cucumber Root Colonizatmentioning
confidence: 95%
“…asburiae + half dose of N2 treatment increased the oil yield in the first cut of plant to (1.03%). Swamy et al (2016) reported that the essential oils have high potential in the field of biomedicine as they effectively destroy many of bacterial, fungal, and viral pathogens, due to several types of aldehydes, terpenes, phenolics and other antimicrobial compounds so that the essential oils are effective against a diverse range of pathogens.…”
Section: -Chemical Analysismentioning
confidence: 99%
“…This communication is of extreme significance for the persistence and colonization of applied bacteria in the plant rhizosphere. Numerous investigations have been executed to see persistence of inoculated bacteria, especially through labelling of inoculated bacterial strains with a marker gene, for example gfp encoding green fluorescent protein, gusA encoding ß-glucuronidase and so forth (Swamy et al, 2016).…”
Section: Rhizoremediation: Use Of Rhizobacteria To Enhance Hydrocarbomentioning
confidence: 99%